2010
DOI: 10.1007/s10995-010-0718-0
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Trends and Predictors of Infant Sleep Positioning in South Carolina, 1996–2007

Abstract: This paper examines racial differences in trends and predictors of prone and lateral infant sleep positioning among South Carolina mothers and infants. Pregnancy Risk Assessment Monitoring System data were used to analyze linear trends in prone, lateral, and supine infant sleep positioning among 14,648 mother-infant pairs from 1996 to 2007. Logistic regression models were used to examine the predictors of prone and lateral positioning among 9,015 mother-infant pairs from 2000 to 2007. From 1996 to 2007, white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…15 To reduce infant mortality, further education about safe sleep, specifically aimed at African American and low-income populations, is needed. [16][17][18][19] The education must include information about safe sleep position as well as safe sleeping environment. 6 Research suggests that reading materials do not influence African American mothers' choice in sleep position for their infants.…”
Section: Introductionmentioning
confidence: 99%
“…15 To reduce infant mortality, further education about safe sleep, specifically aimed at African American and low-income populations, is needed. [16][17][18][19] The education must include information about safe sleep position as well as safe sleeping environment. 6 Research suggests that reading materials do not influence African American mothers' choice in sleep position for their infants.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by Smith et al looking at race and infant sleep positioning in South Carolina, 60.2% of white, non-Hispanic infants were found to be placed in the supine sleep position whereas only 38.8% of black, non-Hispanic infants were positioned supinely in 2004. [26] In another study by Colson et al [27] mothers of black race were found to be 3 times more likely to practice infant bed sharing.…”
Section: Original Articlementioning
confidence: 94%
“…3,5 Interestingly, having a non-native Dutch father was associated with a lower risk of PHP, which supports the suggestion that ethnic background and cultural habits may play a role in the genesis of PHP. 18,26 PHP was only associated with two perinatal risk factors:…”
Section: Discussionmentioning
confidence: 99%